FRAMING PEMBERITAAN ISU POLIGAMI DALAM TAYANGAN NARASI NEWS ROOM ‘MENGUAK SISI LAIN MENTORING POLIGAMI BERBAYAR’ (E-Jurnal Medium, 2022)
The Youtube Narasi Newsroom show entitled ‘Menguak Sisi Lain Mentoring Poligami Berbayar’ had become trending 4 in the trending column of Youtube Indonesia in November 2021. The show is an in-depth coverage of a mentoring practice that is closely related to Polygamy in Indonesia. Narasi as a mass media plays an important role in describing a problem as is done in this show. But the mass media also do framing. Framing is something the mass media do to see content into an impression. This study will see how the framing is carried out by Narasi Newsroom on the show ‘Menguak Sisi Lain Mentoring Poligami Berbayar' on the issue of polygamy. In this analysis, the framing model of Robert N. Entman will be used. The results of this study indicate that the Newsroom Narrative raises a number of facts that tend to be negative from polygamy and the polygamy campaign.